"Having attitude" : nurses' perceptions of the qualities and skills needed to successfully nurse the 10-24 year old client : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - MacDonald, Susan (Massey University, 1998)
This thesis presents a grounded theory study following Glaser's methodological stance. It explores nursing of the 10-24 year old client through interviews with thirteen registered nurses. The participants worked in a variety of clinical settings including community, hospital and specific adolescent services. From the analysis of the data emerged the complexity of the nurses' work with the chosen age group. The study identifies that the quality of the nurse/client encounter may enable the young person to feel accepted and to be empowered to make their own health choices. This thesis identifies how 'Having Attitude' is seen by the nurse participants as critical in the care of the young person. 'Having Attitude' is about the nurse balancing the dependence/independence needs of the young person with their family and peers, and about being acceptable to the client. This results from the work of the nurse which is characterised by the nurse 'being competent' and 'being supportive' whilst taking into account all of the socio-political factors that effect the nurse's working situation. The socio-political context impacts upon the young person's life in terms of the types of health issues they have, and the availability and affordability of appropriate health services. It also impacts on the environment in which the nurse works, in terms of the complexity of the concerns with which young people present, current health reforms and funding issues. The nurse needs to have a broad knowledge base and ability to work within a complex situation. Nurses believe they can make a difference to the young person's health experience when they are supportive, competent and 'have attitude'.
Keywords: Nurse and patient; Youth -- Health and hygiene